NEW SELF-GRAVITATIONAL OSCILLATORY EIGENMODE PATTERNS OF SOLAR PLASMA WITH BOLTZMANN-DISTRIBUTED ELECTRONS - P. K. Karmakar; B. Borah (European Scientific Journal, ESJ, 2014)
We attempt to propose a simplified theoretical model to study new stationary states of the nonlinear self-gravitational fluctuation dynamics of the solar plasma with the zero-inertia electrons against weakly nonlinear perturbation within the framework of the Jeans homogenization assumption. This is based on a bi-fluidic approach with the thermal electrons treated as the Boltzmann-distributed species. The joint effects of space-charge polarization, sheath-formation, and bi-layer plasma-boundary interaction through gravito-electrostatic interplay in a spherically symmetric geometry are considered. Applying a standard multiscale technique, a unique form of extended Korteweg-de Vries-Burger (e-KdVB) equation with a new selfconsistent linear sink is methodologically developed. The origin of the unique sink lies in the spherically symmetric self-gravity contributed by the massive ions. A numerical shape-analysis with multi-parameter variation depicts the co-existence of two distinct classes of new eigenmode excitations. The fluctuation patterns evolve as oscillatory soliton-like and oscillatory shock-like patterns in judicious plasma conditions under the adiabatic electronic response. Their oscillations, arising due to resonant and non-resonant coupling phenomena with the background spectral components, get gradually damped out due to the sink. This scientific study allows us to conjecture that the model supports self-gravitational solitary (shock) waves having tails (fronts) composed of a sequence of slightly overlapping solitons with smoothly varying characteristic parameters. Our results are compared with the earlier theoretical model predictions, on-board multispace satellite data and spacecraft observations highlighting tentative future scopes.